Effects of moxa smoke on monoamine neurotransmitters in SAMP8 Mice - Xu, Huanfang (2014)
Objectives. To investigate the anti-aging effects of moxa smoke on SAMP8 mice. Methods. Using 2 × 3 factorial design, exposure length (15 or 30 minutes daily), and concentration (low, 5–15mg/m3; middle, 25–35mg/m3; high, 85–95mg/m3), 70 SAMP8 mice were randomly assigned, n = 10/group, to a model group or one of six moxa smoke groups: L1, L2, M1, M2, H1, or H2. Ten SAMR1 mice were used as normal control. Mice in moxa smoke groups were exposed to moxa smoke at respective concentrations and exposure lengths; the model and normal control mice were not exposed. Cerebral 5-HT, DA, and NE levels were determined using ELISA. Results. Compared to normal control, the model group showed a significant decrease in 5-HT, DA, and NE. Compared to model group, 5-HT and NE were significantly higher in groups L2,M1, andM2 andDA was significantly so in L2 andM1. 5-HT,DA, andNE levels were the highest in groupM1 amongmoxa smoke groups. Amarked exposure length × concentration interaction was observed for 5-HT, DA, and NE. Conclusion. Moxa smoke increases monoamine neurotransmitter levels, which varies according to concentration and exposure length. Our finding suggests that the middle concentration ofmoxa smoke for 15 minutes seems the most beneficial.